Artificial Intelligence and Ethical Practices: A Study in the Realm of Translatiоn - Al-Kadery, Suad Abdulaziz Khalil; Almotiry, Mohammad Moghim G (International Journal of Linguistics and Translation Studies, 2025)
Of late, translation work has occupied pride of place in businesses and professions and other activities carried out by humans due to increasing global interaction for various reasons such as globalisation, tourism (adventure, travelling and pilgrim tourism being the most popular ones) becoming a passion and quest to know other peoples’ living styles and their cultures, and visit historical places and monuments preserved as heritage. With every journey and every deal, translation powers the global exchange, proving that language is the ultimate connector. Said differently, translation has occupied a very important place in business professions and other activities due to increasing global interaction. Artificial Intelligence has been drafted to help in translation work with its LLM tools. Bias in AI, data privacy, transparency, and the impact that AI will have on professional translations and its professionals are key concerns in contemporary times. The study aimed to investigate and determine the optimal integration of AI within the translation industry, addressing potential biases of LLMs. The study employed mixed methods as it used a survey with 112 professional translators followed by semi-structured interviews to gather data on six factors that have come into prominence in the era of AI tools in translation. Results indicated that though AI tools are seen as a great aid in translation, Saudi translators use them with great caution, especially in the business translation domain given the many caveats that such translation comes with. Also evident that cultural and regional sensitivity is a major onus of the translation professionals, AI tools are not viewed as fully reliable in this context and human intervention alongside AI tools in translation is preferred. The study concludes with recommendations pertinent to translation professionals, teachers, policymakers, and business houses. Ethical concerns, however, remain a major concern for professionals as data privacy is not assured in their use.